"It's Their World, so You've Just Got to Get Through": Women's Experiences of Parole Governance. (April 2015) - Opsal, Tara
This article brings together research on parole governance with women's experiences of reentry. In particular, drawing on longitudinal qualitative interviews with a group of women leaving prison and returning to their communities, the present study highlights the way parole structures women's reintegration efforts post-incarceration. The women's experiences highlight how parole governance intersects, conflicts with, and complicates their efforts to return to their communities and transition out of the gaze of the penal state.